Role of hysterolaparoscopy in the evaluation of female infertility in a tertiary care centre - Parihar, Bharti Choudhary; Gowri, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility is one of the most important and underappreciated reproductive health problems in developing countries. Inability to conceive bears a social stigma which causes societal repercussion and personal suffering. The advent of hysterolaparoscopy have redefined the evaluation and treatment of infertile women. Study aimed to assess the role of hysterolaparoscopy in the evaluation of female infertility. Methods: This prospective observational study was done in the department of obstetrics and gynaecology, Gandhi Medical College, Sultania Zanana Hospital, Bhopal, during the period between 1st December 2016 to 30th November 2017. 104 infertile patients either with primary or secondary infertility were included after thorough evaluation. Results: Out of 104 infertile patients, 82(78.8%) women had primary infertility and rest 22(21.1%) women had secondary infertility. In primary infertility group, most common laparoscopic finding was PCOD in 24(29%) women and in secondary infertility group, tubal blockage was seen in 9(40%) women. The most common pathology seen in hysteroscopy was submucous fibroid in 6(7.3%) women with primary infertility, whereas in secondary infertility group, synechiae was found in 2(9%) patients and septum was seen in 1(4.5%) patient. Out of 104 patients, 33 (31.7%) patients underwent various interventions. The most common intervention was ovarian drilling for PCOS in 21(63.3%) patients followed by hysteroscopic cannulation in 5(15.5%) patients. Conclusions: Hysterolaparoscopy is a very useful tool that can detect various structural abnormalities in multiple sites like uterus, tubes, ovaries and peritoneal cavity in the same sitting. When done by experienced hands and proper selection of patients, hysterolaparoscopy can be considered as a definitive investigative procedure for evaluation of female infertility.